The Impact of Post-Modernism and of Post-Truth on Indonesian Society and the Christian Mission: a Philosophical-Theological Perspective - Donatus, Sermada Kelen; Virgenius Setiawan, Charles (Litbang STFT Widya Sasana Malang, 2025)
The background of writing this article was author’s presentation of the topic during the symposium of Asia-Pacific Association of Mission Researchers (ASPAMIR) held in Widya Mandira Catholic University, Kupang, NTT, Indonesia, on 22nd-25th, 2022 under the main theme of the symposium “Post-Modernism and Post-Truth and the Christian Mission”. The author is a member of this association, and the purpose of bringing this topic in the journal of Studia philosophica et theologica is to introduce the meaning of post-modernism and of post-truth with their impact on Indonesian society and to interpret the Christian mission by doing the narrative theology in accordance with the present situation and condition of Indonesian society. The method the author has used is to show up the empirical facts produced by the impact of post-modernism and of post-truth on Indonesian society and to deepen these empirical facts under the light of philosophical theological views. The result of elaborating this topic is found in the last part of the article concerning an effort to respond on the saving power of God working in the midst of Indonesian society nowadays